Il turismo di massa “come ornamento” nella prospettiva critica di Siegfried Kracauer. Con due brevi focus cinematografici - Spinosa, Domenica (Scenari, 2025)
This article aims to address the issue of modern tourist travel, by first, reconsidering Siegfried Kracauer’s critical positions from an article written in 1925. Kracauer insists that among the goals of bourgeois society, which tends more and more towards capitalism and the perfection of the means of mass production, is a veritable transformation of both the form and the content of travel, which is reduced to a mere and simple movement from one place to another. The Kracauer’s theses is also useful as premise for the second part of the article, in which he proposes a brief analysis of two films in which tourist travel is a central experience: WestWorld (1973) by Micheal Crichton and Le vacanze intelligenti (1978) by Alberto Sordi. The filmic occasion attempts to show how cinema has tried to narrate the subject in question from a critical-social point of view.